ANALISIS KERENTANAN KAWASAN PERMUKIMAN PADA KAWASAN RAWAN BANJIR DI BAGIAN HILIR SUNGAI SARIO - Ivone Paula Bungkolu; Grace A. J. Rumagit; Rine ., Kaunang (AGRI-SOSIOEKONOMI, 2017)
The objectives of this research are: (1) Analyzing any susceptibility factors that can influence people downstream of Sario River to settle or not stay in settlements located in flood prone areas, (2) Reviewing the policy of flood-prone settlement management what is most effective in overcoming the existing flood problems at the site. This research was conducted in September until November 2017. Sampling method used was purposive sampling method. Analytical technique used in this research using quantitative method that is using logistic regression. The results of this study indicate that (1) the most influencing factor of the person staying in the flood prone area downstream of the Sario River is the social susceptibility factor precisely the social ties, ie the close kinship between the members of the community in the location. (2) Furthermore, the most appropriate government program for dealing with settlements of the lower flood prone areas of the Sario River is through the creation of a retaining river basin or river dredging.